Perbandingan Efisiensi dengan Algoritma Sorting dalam Penentuan Jarak (Studi Kasus: Pet Shop di Bandar Lampung) - Puspita Sari, Yuni; Ali, Rionaldi; Rajasa, Arya (TEKNIKA, 2022)
Pet Shop is a place to sell pets along with equipment and supplies for animal care. In Bandar Lampung there are approximately 100 Pet Shops which are widely spread, both small and large Pet Shops. However, not all people know the Pet Shop locations, starting from the closest one or having complete facilities and services from the existing Pet Shop. They tend to have difficulty when it comes to grooming their pets or finding their pet's food needs. This application was designed using the prototype development method and in sorting the closest distance at the Pet Shop using the Selection Sort and Insertion Sort algorithms. This application is dynamic because the data can change according to the increase or decrease in the Pet Shop registered in the application. The result of this study was an application that displayed an information medium to determine the distance of the closest and furthest Pet Shop, tables and memory graphs that function to determine the memory used and display a time graph. From the results of the comparative analysis of the efficiency of the Selection Sort and Insertion Sort algorithms, it was found that the Selection Sort algorithm was the best algorithm that was effective and efficient in dealing with the data sorting problems. This application was tested using the black box testing with the test components, namely, loading performance functions, and 3 device interfaces.